2010
DOI: 10.1371/journal.pone.0009254
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity of CD4+ T-Effector Cells to CD4+CD25+ Treg Suppression Compensates for Reduced Treg Number in Asymptomatic HIV-1 Infection

Abstract: BackgroundIn HIV infection, uncontrolled immune activation and disease progression is attributed to declining CD4+CD25+FoxP3+ regulatory T-cell (Treg) numbers. However, qualitative aspects of Treg function in HIV infection, specifically the balance between Treg cell suppressive potency versus suppressibility of effector cells, remain poorly understood. This report addresses this issue.Methodology/Principal FindingsA classic suppression assay to measure CD4+CD45RO+CD25hi Treg cells to suppress the proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 57 publications
(105 reference statements)
3
38
0
1
Order By: Relevance
“…However, it has been demonstrated that the relative frequency of Treg cells within the CD4 T cell population as a whole appears to increase during HIV infection while at the same time, the absolute numbers of Tregs decline(Schulze Zur, Thomssen et al, 2011). This is supported by several studies which indicated a gradual decline in Treg absolute numbers during HIV pathogenesis (Jiao, Fu et al, 2009;Prendergast, Prado et al, 2010;Thorborn, Pomeroy et al, 2010;Cao, Jamieson et al, 2009). In particular, in primary HIV infection in untreated individuals, HIV-specific Treg cells and suppressive activity decreased over a 24 month follow-up period (Kared, Lelievre et al, 2008).…”
Section: Treg In Hiv Infectionmentioning
confidence: 96%
“…However, it has been demonstrated that the relative frequency of Treg cells within the CD4 T cell population as a whole appears to increase during HIV infection while at the same time, the absolute numbers of Tregs decline(Schulze Zur, Thomssen et al, 2011). This is supported by several studies which indicated a gradual decline in Treg absolute numbers during HIV pathogenesis (Jiao, Fu et al, 2009;Prendergast, Prado et al, 2010;Thorborn, Pomeroy et al, 2010;Cao, Jamieson et al, 2009). In particular, in primary HIV infection in untreated individuals, HIV-specific Treg cells and suppressive activity decreased over a 24 month follow-up period (Kared, Lelievre et al, 2008).…”
Section: Treg In Hiv Infectionmentioning
confidence: 96%
“…55,90 Most studies, however, were not able to discriminate the actual Treg potency from the sensitivity of effector cells to Treg suppression. To address this question, Treg activity was tested in both autologous and allogeneic systems in which Tregs from patients and healthy donors were cocultured with effector cells from a unique donor and vice versa.…”
Section: T-cell Sensitivity To Treg-mediated Suppressionmentioning
confidence: 99%
“…Such a relative expansion of Treg accompanied by their depletion in absolute number has been described in HIV infection (7,(36)(37)(38)(39)(40). However, controversial findings have been reported on percentages and numbers of Treg in HIV-1-infected humans or SIV-infected macaques (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 88%
“…[2][3][4][5][6]. Some groups found a lower frequency and absolute number (7)(8)(9)(10) of circulating Treg, whereas others reported them to be increased (11)(12)(13). Contrasting results were also obtained for Treg in lymphoid organs (2,14).…”
mentioning
confidence: 99%